บทวิเคราะห์คำวินิจฉัยของศาลรัฐธรรมนูญที่ 50/2542 เกี่ยวกับร่างพระราชบัญญัติทุนรัฐวิสาหกิจ พ.ศ. ... - สกาวเดือน ลิ่มพงศธร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
Whereas Section 268 of the Constitution of the Kingdom of Thailand (B.E. 2540) has affirmed that the decision of the Constitution Court shall be final and binding on the National Assembly, Council of Ministers, Courts and other State organs ; no organ can review the decision of the Constitution Court, although it effects the principles of law and the interest of the country and the public, e.g. the decision of the Constitution Court no. 50/2542 This thesis intends to study the decision of the Constitution Court no. 50/2542 regarding the Corporatization Bill B.E. … to see whether it is consistent and in compliance with the provisions of the Constitution. Furthermore, it allows us to see how the consequence led by ratio decidendi pertaining to such decision effects principles of law and the interest of the country and the public in order to search for resolving problems and defects that have occurred. The study finds that first, raising an issue in making the decision of the Constitution court no. 50/2542 was based on the issues in the petition without any comprehensive consideration of the actual problem resulting from the Corporatization Bill B.E. … and it result in the fact that such decision cannot respond to the actual problem, and secondly, ratio decidendi pertaining to such decision affects the principles of law in many aspects: the destruction of the principle of check and balance under the Constitution, of the legislative procedure the Constitution, and the principle of hierarchy of laws. The author has the opinion that these destructions were caused 2 problems – the qualification of judges of the Constitutional Court and the clarity provisions of laws concerned. As for the problem of the qualifications of judges of the Constitutional Court, the author recommends that the qualifications of the candidate for the judgeship of the Constitutional Court be specified, for instance, he or she should have the juristic methodology, knowledge, experience and expertise in public laws. In regarding to the lack of clarity of the provisions of laws concerned, the author recommends that a special commission be established so that it shall examine the provisions of laws and make certain that they follow to the actual spirit of each law, and to add provisions to the Corporatization Bill B.E. 2542 to prevent any evitable damage to be caused by ambiguity and affect the interest of the country and the public.